Role of Extracellular Vesicles in Cellular Cross Talk in Malaria - Babatunde, Kehinde Adebayo; Yesodha Subramanian, Bibin; Ahouidi, Ambroise Dioum; Martinez Murillo, Paola; Walch, Michael; Mantel, Pierre-Yves (Frontiers in Immunology, 2020)
Malaria infection caused by the Plasmodium species is a complex disease in which a fine balance between host and parasite factors determine the outcome of the disease. While in some individuals, the infection will trigger only a mild and uncomplicated disease, other individuals will develop severe complications and eventually die. Extracellular vesicles (EVs) secreted by infected red blood cells as well as other host cells are important regulators of the fine balance that determine the disease severity. EVs represent an important mode of intercellular communication by serving as vehicles for transfer between cells of membrane and cytosolic proteins, lipids, and RNA between parasites and between parasites and host. EVs not only modulate the immune response, they also mediate cellular communication between parasites to coordinate the transmission stage. Here we review the recent progresses in understanding EV roles during malaria.